Degree of severity of dysphonia through vocal acoustic analysis in teachers from two institutions of the early childhood care strategy. (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2019)
INTRODUCTION: The aim of the study is to identify the prevalence and factors related to dysphonia through the vocal acoustic, in female documents ranging from 20 to 50 years old. METHODS: Study of quantitative type, of transversal and descriptive cut, in the instruments of evaluation scale RASATI, index of vocal disadvantage and pharyngeal occupational record. RESULTS: The statistical analysis of the information of the values of normality with the evaluation tools used in the sample, was cor-related with the representation and description of the results thrown according to the evaluation, the prevalence of dysphonia of the sick teachers is of 9%. ANALYSIS AND DISCUSSION: The vocal quality and the degree of severity of dysphonia were classified according to the relationship of the evaluation criteria in the established instruments and the perception with the RASATI scale, with the vocal disadvantage index to identify the degree of dysphonia in the population. CONCLUSIONS:There is a prevalence of dysphonia in teachers, associated with the acquisition of behaviors or habits that affect risk factors on exposed in the professional task
Keywords: Dysphonia; Voice quality; risk factors; teachers; occupational disease